American Masculinity under the Pressure of Changes - Ondřej Frunc (Gender a Výzkum)
In their publication, Yasemin Besen-Cassino and Dan Cassino focus on capturing the basic strategies by which men in the US compensate for changes in the perception of their masculinity. They draw on a large amount of quantitative and qualitative data, which I consider to be one of the great contributions of this publication. They outline a basic overview of strategies that can be significantly expanded in further research and further deepen knowledge about the direction different men take if they feel their own masculinity is threatened. Their book Gender Threat: American Masculinity in the Face of Change (2022) is still a relevant text for the study of masculinity in the US. I believe that by following their ideas we can be inspired in the research of masculinity in Europe and in the Czech Republic.